CuBi2O4 Synthesis, Characterization, and Application in Sensitive Amperometric/Voltammetric Detection of Amoxicillin in Aqueous Solutions - Raluca Dumitru (m.Vodă); Sorina Negrea; Cornelia Păcurariu; Adrian Surdu; Adelina Ianculescu; Aniela Pop; Florica Manea (Nanomaterials, 2021)
CuBi2O4 synthesized by thermolysis of a new Bi(III)-Cu(II) oxalate coordination compound, namely Bi2Cu(C2O4)4·0.25H2O, was tested through its integration within carbon nanofiber paste electrode, namely CuBi/carbon nanofiber (CNF), for the electrochemical detection of amoxicillin (AMX) in the aqueous solution. Thermal analysis and IR spectroscopy were used to characterize a CuBi2O4 precursor to optimize the synthesis conditions. The copper bismuth oxide obtained after a heating treatment of the precursor at 700 °C/1 h was investigated by an X-ray diffraction and scanning electron microscopy. The electrochemical behavior of CuBi/CNF in comparison with CNF paste electrode showed the electrocatalytic activity of CuBi2O4 toward amoxicillin detection. Two potential detections, with one at the potential value of +0.540 V/saturated calomel electrode (SCE) and the other at the potential value of −1.000 V/SCE, were identified by cyclic voltammetry, which were exploited to develop the enhanced voltammetric and/or amperometric detection protocols. Better electroanalytical performance for AMX detection was achieved for CuBi/CNF using differential-pulsed and square-wave voltammetries than others reported in the literature. Very nice results obtained through anodic and cathodic currents recorded at +0.750 V/SCE and −1.000 V/SCE in the same time period using a pseudo multiple-pulsed amperometry technique showed the great potential of the CuBi/CNF paste electrode for practical applications in amoxicillin detection in aqueous solutions.